Pengaruh Ketidakpastian Lingkungan dan Strategi Bisnis Terhadap Kinerja Manajerial dengan Karakteristik Sistem Informasi Manajemen Sebagai Variabel Intervening (Studi Empiris Pada Perusahaan Jasa Perhotelan di Kota Padang dan Bukittinggi) - Lisa Khairina Putri (Universitas Negeri Padang, 2014)
This study aims to obtain empirical evidence about the extent of influence of environmental uncertainty and business strategy on managerial performance with characteristic management accounting system as intervening variables. The population is manager of hotel in the city of Padang and Bukittinggi. Collection methods using questionaires. Analizing data used SEM (structural equation modeling) by Lisrel 8.72 program. The result of this study indicate: (1) environmental uncertainty have a significant positive effect on broadscope information of characteristic management accounting system variable. (2) The prospector business strategy have insignificant effect on broadscope information of characteristic management accounting system variable. (3) Broadscope information of characteristic management accounting system variable have a significant positive effect on managerial performance. (4ₐ) ) Environmental uncertainty have a significant positive effect on managerial performance if mediating with broadscope information of characteristic management accounting system. (4b). The prospector business strategy have a significant negative effect on managerial performance if mediating with broadscope information of characteristic management accounting system. Suggestions for next researchers are giving full attention to other factors that affected the company performance and as well as increasing the number of samples. Keyword: environmental uncertainty, business strategy, characteristic of management accounting system, managerial performance